2006
DOI: 10.1074/jbc.m513814200
|View full text |Cite
|
Sign up to set email alerts
|

A Minimal Promoter for TFIIIC-dependent in Vitro Transcription of snoRNA and tRNA Genes by RNA Polymerase III

Abstract: The Saccharomyces cerevisiae SNR52 gene is unique among the snoRNA coding genes in being transcribed by RNA polymerase III. The primary transcript of SNR52 is a 250-nucleotide precursor RNA from which a long leader sequence is cleaved to generate the mature snR52 RNA. We found that the box A and box B sequence elements in the leader region are both required for the in vivo accumulation of the snoRNA. As expected box B, but not box A, was absolutely required for stable TFIIIC, yet in vitro. Surprisingly, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 68 publications
0
25
0
1
Order By: Relevance
“…115 Importantly, it was also experimentally shown that the A-box of the SNR52 gene is sufficient for directing S. cerevisiae RNAP III transcription, supporting a functional specialization of submodules within TFIIIC into GTF (τA) and transcriptional activator (τB). 120 In accordance with this model, the B-Box element within the transcribed regions of genes with type 2 promoter elements may be considered as an enhancer element. Since the subunit composition of yeast and human TFIIIC has been conserved during evolution, 52 it can be assumed that this point of view may also hold true for human RNAP III transcription although this has not yet formally been shown.…”
Section: Rnap III Genes With Promoters Within the Transcribed Sequencementioning
confidence: 99%
“…115 Importantly, it was also experimentally shown that the A-box of the SNR52 gene is sufficient for directing S. cerevisiae RNAP III transcription, supporting a functional specialization of submodules within TFIIIC into GTF (τA) and transcriptional activator (τB). 120 In accordance with this model, the B-Box element within the transcribed regions of genes with type 2 promoter elements may be considered as an enhancer element. Since the subunit composition of yeast and human TFIIIC has been conserved during evolution, 52 it can be assumed that this point of view may also hold true for human RNAP III transcription although this has not yet formally been shown.…”
Section: Rnap III Genes With Promoters Within the Transcribed Sequencementioning
confidence: 99%
“…Correspondingly, the A box has the characteristics of a core promoter element (proximity to TSS, role in PIC assembly) while the B box resembles an enhancer-like element. In support to this view, an A box has been shown to suffice for faithful and efficient in vitro transcription of mutated Pol III templates carrying no functional B box, thus sketching a scenario in which a minimal TFIIIC/TFIIIB assembly module, comprising an A box and possible upstream elements (such as a TATA and/or an Initiator-like element; see next section) surrounding the TSS, is reminiscent of the composite organization of RNA polymerase II core promoters (Guffanti et al, 2006a). As an integral part of such a core promoter module, the A box-interacting sub-complex of TFIIIC participates in TSS selection together with the TATA-box binding protein (TBP) which is part of TFIIIB (Joazeiro et al, 1996).…”
Section: The a Box As A Fundamental Core Promoter Element In Pol III mentioning
confidence: 92%
“…Interestingly such an effect (usually weakening the terminator, and becoming apparent only in the presence of T stretches of minimal length) can be exerted both by very short sequence stretches just downstream of the poly(dT) and by upstream sequences, suggesting at least two possible mechanisms of modulation, one involving contacts between the front end of polymerase and downstream DNA, the other possibly involving an allosteric action on polymerase of nascent RNA (Braglia et al, 2005). The strongest known termination-weakening context is the one occurring within the SNR52 transcription unit of S. cerevisiae, in which a T 6 stretch located between the A box and the B box of a tRNA-like leader sequence is largely read through by Pol III, a behavior which is determinant for the efficient production of the encoded snoRNA (Braglia et al, 2005;Guffanti et al, 2006a).…”
Section: Pol III Termination Signals: Strengths and Weaknesses Of T-rmentioning
confidence: 99%
“…UM2 snoRNA loci give rise to primary transcripts that resemble the dicistronic primary tRNA-snoRNA transcripts found in yeast and plants, which are cleaved by RNase Z, thereby generating the mature snoRNAs with 59 monophosphate termini (Kruszka et al 2003;Guffanti et al 2006). The processing mode of UM2 snoRNA primary transcripts is not known but is likely to generate mature snoRNAs with 59 monophosphate termini (since both endonuclease and exonuclease activity creates this type of 59 terminus).…”
Section: Discussionmentioning
confidence: 99%